SINE-derived short noncoding RNAs: their evolutionary origins, molecular mechanisms, and physiological significance - Yoshimoto, Rei; Nakagawa, Shinichi (Frontiers in RNA Research, 2023)
Short Interspersed Elements (SINEs) comprise a significant portion of the genomes of higher eukaryotes, including humans and mice. This review focuses on SINE-derived noncoding RNAs (ncRNAs), particularly BC1, BC200, and 4.5SH RNA, which are expressed abundantly and in a species-specific manner. These ncRNAs seem to have independently evolved their functions during evolutionary processes: BC1 and BC200 have become cytoplasmic translation inhibitors, while 4.5SH RNA has developed into a nuclear ncRNA that regulates splicing. This review delves into the unique roles of these ncRNAs, with a special emphasis on the recently discovered splicing regulation function of 4.5SH RNA. Furthermore, we discuss their evolutionary trajectories and potential implications for understanding the complexities of gene regulation.